A Nonlinear Trajectory Tracking Controller for Mobile Robots with Velocity Limitation via Fuzzy Gains - Resende, Cassius Z. (2013)
This paper proposes a fuzzy controller for trajectory tracking with unicycle-like mobile robots. Such controller uses two Takagi–Sugeno (TS) fuzzy blocks to generate its gains. The controller is able to limit the velocity and control signals of the robot, and to reduce the errors arising from its dynamics as well. The stability of the developed controller is proven, using the theory of Lyapunov. Experimental results show that the use of the proposed controller is attractive in comparison with the use of a controller with fixed saturation function.